ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE DAN FINANCIAL LEVERAGE TERHADAP KINERJA KEUANGAN BANK UMUM SYARIAH DENGAN VOLUME PEMBIAYAAN SEBAGAI VARIABEL MODERASI - Juna, Junaedi (Jurnal Riset Keuangan Dan Akuntansi, 2015)
This research is a quantitative study which aims to analyze the effect of the implementation of good corporate governance ( GCG ) and financial leverage on the financial performance of Islamic Banks in Indonesia with a financing volume as a moderating variable. GCGCGPI proxy of the composite value, proxied by the DER financial leverage and financial performance proxied by ROA. The population in this research that the entire Islamic Banks in Indonesia in the span of 2009 to 2012. Determination of the sample by using purposive sampling the object obtained 11 studies analyzed panel data regression models with ordinary least squares (OLS) regression analysis and Moderation.The results of this study indicate that the GCG positive effect on financial performance, financial leverage has no effect on financial performance, financing volume moderate the relationship between corporate governance and financial performance, financing volume does not moderate the relationship between financial leverage and financial performance.Based on the analysis in this study, the following suggestions are presented: (1) For Researchers: to increase the number of observational studies, the researchers can further augment the study period so that the collected data is becoming more and research results will be better, researchers can further add other independent variables are predictable effect on the financial performance of the BUS and increase the number of variables that can be predicted to interfere with the relationship between the independent variables on the dependent variable, further research can be conducted by comparing the corporate governance of Islamic banks with conventional banks; (2) For Islamic banks: Banks can observe about the state of corporate governance in order to continuously improve the quality GCGGCG because it can improve the quality of the bank's financial performance.